Singir of Syekh Muallim: Verses of Soteriology for Contemporary Muslim Youth from a Gadamerian Hermeneutical Perspective - Mohamad Wahyu Hidayat; M. Sa'i; Karsiwan (Journal of Islamic History, 2026)
This study aims to examine the content of Syekh Muallim's poems that contain moral teachings for the younger generation of Muslims. Syekh Muallim (1920s-1995) was known as a cleric and leader of the Al-Fiil Kesugihan Islamic boarding school in Cilacap Regency, Central Java, with his expertise in creating soteriological poems for his students. The results of the study show that the entire text of Syekh Muallim's poems, which were found to be composed in the form of nadzom or verses, consists of 17 chapters and a total of 558 lines. There are several parts of Syekh Muallim's poetry that are similar to Kyai Bisri Musthofa's Ngudi Susila, although there are similarities, Syekh Muallim made slight changes to the text to suit the Banyumasan dialect. Overall, the verses of Syekh Muallim's poem serve as comprehensive soteriological and pedagogical guidelines. The text not only teaches the importance of devotion and obedience in the social and spiritual hierarchy, but also provides a blueprint for the formation of a holistic Muslim character to achieve worldly and spiritual salvation. Specifically, the text studied in this research is divided into three discussions: the chapter on the fortune of creatures, the chapter on mudha-mudhi, and the chapter on manners. These findings are expected to provide insight into the pedagogical richness of the pesantren literary heritage and its relevance to the character building of the young Islamic generation, especially in a modern era full of social challenges. REFERENCES Aprilia, N. (2024). Pemikiran Gramatikal Bahasa Arab K.H. Ahmad Mu’allim: Telaah Atas Kitab Tāshil al Ṭalabah fi Naẓm al jurūmiyyah al jāwiyyah. UIN Prof. K.H. Saifuddin Zuhri. Azra, A., Afrianty, D., & Hefner, R. W. (2010). Pesantren and madrasa: Muslim schools and national ideals in Indonesia. In Schooling Islam: The Culture and Politics of Modern Muslim Education (pp. 172–198). Baroroh-Baried, S., & Dkk. (1985). Pengantar Teori Filologi. Jakarta: Pusat Pembinaan dan Pengembangan Bahasa Depdikbud. Charoline, C., & Ariana, M. (2024). Doktrin Keselamatan (Soteriologi). Pediaqu: Jurnal Pendidikan Sosial Dan Humaniora, 3(3), 1970–1977. Eco, U. (1992). Interpretation and Overinterpretation: World, History, Texts. Cambridge, UK: Cambridge University Press. Fathurahman, O. (2018). Female Indonesian Sufis: Shattariya Murids in the 18th and 19th Centuries in Java. Kyoto Bulletin of Islamic Area Studies, 11, 40–67. Retrieved from https://repository.kulib.kyoto-u.ac.jp/dspace/bitstream/2433/230448/1/I.A.S_011_040.pdf Handayani, E. (2022). Studi Perbandingan Konsep Keselamatan Agama Islam dan Kristen. Universitas Islam Negeri Raden Intan Lampung. Ichwan, M. N. (2019). Qur’anic Soteriology: Doktrin Teologis tentang Keselamatan dan Nasib Pemeluk Agama Lain dalam Perspektif Al-Qur’an. (C. El-Rafi’a, Ed.) (I). Semarang: RaSAIL Media Group. Kusnadi. (2006). Seni Singiran dalam Ritual Tahlilan pada Masyarakat Islam Tradisional Jawa. Imaji, 4(2), 218–231. Muallim. (1994). Ijtimaussyi’ri. Cilacap: Pondok Pesantren Al Fiel. Mudin, M. I., Fikri, M. D., Shobirin, M. M., & Mukharom, R. A. (2021). Hermeneutika Hans-Georg Gadamer: Studi Analisis Kritis Penafsiran Amina Wadud tentang Ayat Kepemimpinan. Intizar, 27(2), 113–126. https://doi.org/10.19109/intizar.v27i2.10104 Muhammad Shohib, & Kholifatus Sa’diyah. (2023). Kriteria Sukses Dalam Al-Qur’an (Kajian Tematik). Jurnal Ilmu Pendidikan Dan Sosial, 2(1), 53–61. https://doi.org/10.58540/jipsi.v2i1.192 Mussaif, M. M., Suyanto, & Rukiyah. (2002). Kedudukan dan Fungsi Singir Bagi Masyarakat Sastra Jawa (Laporan Penelitian). Semarang. Mustaqim, A. (2016). Model Penelitian Tokoh (Dalam Teori dan Aplikasi). Jurnal Studi Ilmu-Ilmu Al-Qur’an Dan Hadis, 15(2), 201. https://doi.org/10.14421/qh.2014.1502-01 Musthofa, B. (1954). Syingir Ngudi Susila. Rembang: Menara Kudus. Retrieved from https://archive.org/details/NgudiSusiloKHBisriMusthofa03Mar2016095913.compressed/mode/2up Ngarifah, I., Basri, H., & Fakhrurrazi, F. (2023). Revitalization of Syingiran as A Strengthening of Sociality and Spirituality of Rural Communities: The Existence of Oral Literature. Sosial Budaya, 20(1), 82. https://doi.org/10.24014/sb.v20i1.22251 Sedyawati, E., & dkk. (2001). Sastra Jawa Suatu Tinjauan Umum. Jakarta: Balai Pustaka. Wibowo, A. G. (2015). Pendidikan Karakter Berbasis Kearifan Lokal di Sekolah. Yogyakarta: Pustaka Pelajar. Wieringa, E. P. (2006). Moral Education Through Islamic Songs in Twentieth-Century Java. In Religious Perspectives in Modern Muslim and Jewish Literatures (pp. 81–99). New York: Routledge Taylor & Francis. https://doi.org/10.11157/rsrr2-2-565 Zuliana, R., & Mujibuddin, M. (2019). Sastra Pesantren Di Arena Sastra Indonesia. In MPSN (pp. 560–575).